Spatiotemporal dynamics of the development of mouse olfactory system from prenatal to postnatal period - Kim, Bo-Ra; Rha, Min-Seok; Cho, Hyung-Ju; Yoon, Joo-Heon; Kim, Chang-Hoon (Frontiers in Neuroanatomy, 2023)
The olfactory epithelium (OE) and olfactory bulb (OB) are the major components of the olfactory system and play critical roles in olfactory perception. However, the embryonic development of OE and OB has not been comprehensively investigated yet. Most previous studies were limited to a specific embryonic stage, and very little is known, till date, about the development of OE. The current study aimed to explore the development of mouse olfactory system by spatiotemporal analysis of the histological features of olfactory system from the prenatal to postnatal period. We found that OE is divided into endo-turbinate, ecto-turbinate, and vomeronasal organs, and that putative OB with putative accessory OB are formed in the early developmental stage. The OE and OB became multilayered in the later developmental stages, accompanied by the differentiation of olfactory neurons. Remarkably, we found the development of layers of olfactory cilia and differentiation of OE to progress dramatically after birth, suggesting that the exposure to air may facilitate the final development of OE. Overall, the present study laid the groundwork for a better understanding of the spatial and temporal developmental events of the olfactory system.